Characteristics of The Extract of Kelubi (Eleiodoxa conferta Buret) and Its Application as Preservant of Mujair Fish (Oreochromis mossambicus) - Atisanto, Victory Sandy; Suter, I Ketut; Diah Kencana, Pande Ketut (Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology); Vol 9 No 1 (2022): Scientific Journal of Food Technology (March), 2022)
The purpose of this study was to see the effect of solvent concentration and maceration time on the extract of Kelubi fruit (Eleiodoxa conferta Burret). Determine the solvent concentration and maceration time that produces the best Kelubi (Eleiodoxa conferta Burret) fruit extract. Determine the soaking concentration of the Kelubi fruit extract (Eleiodoxa conferta Burret) which can increase the longest shelf life of tilapia fish (Oreochromis mossambicus). This research was divided into two stages in the first phase of research on the effect of solvent concentration and maceration time on kelubi fruit extract. The research was conducted in two steps. The first factor is ethanol solvent 70%, 80%, 96% and The second factor maceration time 12 hours, 24 hours, 36 hours. The results showed that 70% ethanol solvent concentration and 24 hours maceration time produced the best kelubi extract with yield 36,68%, phenol content 4,51%, total acid 0,69, vitamin C levels 5837,18 mg AAE / g and pH 1,63. The best treatment was determined based on the highest phenol compound, the highest yield and total acid. Stage II the effect of immersion in a solution of kelubi fruit extract on the longest shelf life of tilapia fish. The second stage of the study was carried out by using a randomized block design method with immersion in a solution of kelubi extract in tilapia fish with a concentration of 10%, 20%, 30%, 40%, 50%. The results of the analysis showed that concentration of 10% could increase the shelf life of fish with the organoleptic test criteria eye appearance of 4,53 (slightly sunken eyes, cloudy cornea, slightly grayish pupils, not glossy gills pink or pale light brown with cloudy mucus), mucus appearance 4,60 (mucus a bit thick, begins to change color), flesh 4,67 (fleshy incisions begin to fade, less strong flesh tissue), smell 4,73 (slight odor acid), texture 4,63 (slightly soft, less elastic), total acceptance of 4,63 (like), with a pH value of 7,7, and total microbes of 2,60E+09.